Síntese e estudo das propriedades fotoluminescentes dos pós de CaTiO3 decorados com α-Ag2WO4 - Teixeira, Mayara Mondego (2016)
The CaTiO3 (CT) and α- Ag2WO4 (AW) are known to have photoluminescent properties, which is favored by the existence of a structural disorder. The combination of these two materials was observed through decoration of CaTiO3 powders with α-Ag2WO4 to evaluate the optical and morphological properties of the new structure. The CT pure was synthesized by the microwave-assisted hydrothermal method (MAH) at 140 ºC in function to the synthesis time (4, 8, 16 e 32 min). The formation of the CT phase with orthorhombic structure and increasing the crystallinity was confirmed by the X-ray diffraction (XRD) and FT-Raman scattering spectroscopy (Raman) techniques. The scanning electron microscopy (FEG-SEM) images show the growth of CT cubes with increased synthesis time. By means of absorption measurement in ultraviolet-visible spectroscopy (UV-vis) was obtained the Egap values of CT samples. The photoluminescent (PL) emission at room temperature was favored for the disordered CT at medium range. This effect can be attributed to the creation of new levels in the forbidden region of band gap, resulting in a contribution of shallow and deep electronic levels. All the CT powders synthesized by HAM were decorated with AW by coprecipitation. The decoration was performed by two coprecipitation synthetic routes. In synthesis (1), it was observed the formation of a non-desired additional phase (CaWO4), which was identified by XRD and Raman techniques. It had a strong influence in PL emission of the compound in green and blue region. It was proposed a different method of synthesis (2), in which the CT and AW powders were previously prepared and then dispersed separately and mixed under vigorous stirring. The XRD and Raman techniques identified the orthorhombic phase of the powders, CT and AW, included in the decorated. The FEG-SEM and TEM showed the presence of AW rods on CT cubes. The PL profile of decorated samples by means of the synthesis (2) was broad band, covering all the visible spectrum, with two maximum emissions at blue and red region.